Breeding of Ducks at Loch Leven, Kinross - Newton, I; Campbell, C R G (Wildfowl, 1975)
1. Loch Leven holds the biggest concentration of nesting ducks in Britain. In 1966-1973 the population consisted mainly of Tufted Duck Aythya fuligula (500-600 pairs) and Mallard Anas platyrhynchos (400-450 pairs), with smaller numbers of Gadwall Anas strepera (25-30 pairs), Wigeon Anas penelope (25-30 pairs), Shelduck Tadorna tadorna (11-13 pairs), Shoveler Anas clypeata (up to ten pairs) and Teal Anas crecca (up to ten pairs). 2. Each spring, pairs of surface-feeding ducks spaced themselves around the shores of the loch, and pairs of Tufted on open water. For nesting, most females of all species then moved to St. Serf's Island, forming one huge colony in about 14 ha of suitable cover. Where the habitat permitted, nests of each species were spaced out regularly, and the spacing patterns of different species were independent, except that normally no two nests of any species were closer than two metres. Nest-spacing was apparently achieved by the females, and at least in Mallard involved fights. It was independent of the earlier spacing of pairs, in which the drakes were active. On both types of spacing each species tolerated other species closer than its own. 3. Ringed females of all species were caught on the island in more than one year, and usually returned to the same limited area to nest. Sometimes a nest-site was used by more than one female in a season. 4. Mallard began earliest each year and had the longest laying season (up to 16 weeks), while Tufted began latest and had the shortest season (up to ten weeks). Other species were intermediate, both in starting date and in length of season, in the order Wigeon, Shoveler and Gadwall. In surface-feeding ducks, repeat laying occurred after the loss of an earlier clutch, but in Tufted apparently not. In all species, mean clutch-size declined through the season. 5. Hatching success was reduced by our disturbance, which caused females to expose their nests to predators. Without disturbance, probably at most 76%-86% of clutches would have hatched in different years. The main egg-predators were Jackdaws Corvus monedula and to a lesser extent Moorhens Gallinula chloropus. Under disturbance, Gadwall were least successful. In all species, hatching success declined through the season, and was attributed at least partly to a seasonal change in the behaviour of the ducks themselves. 6. The hatching success of all species was better inside a large Black-headed Gull Larus ridibundus colony than outside it. This was probably because the gulls kept out other more serious predators. Tufted Ducks nested at greater density inside the gullery than outside, and in one year of exceptionally high density (215 nests in one hectare) its success was worse, not better, than outside. Under such crowding, many multiple clutches were laid and these had reduced hatching success. 7. Survival of young was almost certainly poor at Loch Leven, especially in surface-feeding ducks. Areas suitable for ducklings were restricted. 8. 'Colonial' nesting at Loch Leven was attributed to the proximity of an attractive nesting island to a shoreline and water area large enough for several hundred duck pairs to establish territories in spring.